Expiry of medicines in supply outlets in Uganda - Katabaazi Nakyanzi, Josephine; Kitutu, Freddy Eric; Oria, Hussein; Kamba, Pakoyo Fadhiru (Bulletin of the World Health Organization, 2010)
In developing countries, where budgets for medicines are often tight, the supply cycle needs to be well-managed to prevent all types of wastage, including pilferage, misuse and expiry. This wastage reduces the quantity of medicines available to patients and therefore the quality of health care they receive. At least US$550 000 worth of antiretrovirals and 10 million antimalarial doses recently expired in Uganda’s National Medical Stores (NMS).1,2 The Ugandan pharmaceutical supply system comprises three non-profit wholesalers (one government medical store and two private non-profit ventures) and several private for-profit wholesale pharmacies that supply medicines in bulk to retail units (private retail pharmacies, hospital pharmacies and drug shops). Drug shops are the smallest retail medicine outlets, are supervised by non-pharmacist health-care professionals, and are limited to handling small amounts of over the-counter medicines.
Keywords: Expiry; Medicines; Supply outlets; Uganda